Omnibus Law di Indonesia - Gugun El Guyanie , Okky Alifka Nurmagulita (Prodi Tata Negara (Siyasah) IAIN Langsa, 2021)
This article examines the drafting of the Omnibus Law on the Job Creation Bill, the original purpose of which was to facilitate investment or accelerate the economy. Starting from the disharmony of several overlapping regulations, out of sync between one law and another in the investment sector, a universal sweeping law that contains thousands of articles is needed. This study uses the theory of the formation of laws and regulations and the perspective of legal politics, with juridical analysis, to explain how a process of drafting a law, the principles of formation, and the political dynamics that gave birth to it. This paper emphasizes that the process and politics of the Omnibus Law legislation on the Job Creation Bill has minimal public participation and is not transparent. So the legal product of the Job Creation Law is formally flawed, and materially contains articles that are capitalist in content, opening up investment for investors but on the other hand harming the people. In this study, it was also found that the Omnibus Law of the Job Creation Act was born with more character instrumentalist-oligarchic, where the government transplants the Omnibus Law solely as a short-term pragmatic option to spread the 'red carpet' for investors. In other words, the Omnibus Law fails to create an instrumentalist-democratic character, which is oriented towards fulfilling and strengthening the values ​​of the rule of law which is long-term oriented while at the same time creating a sustainable participatory-democratic climate.